ENTREPRENEUR SKILL DAN MARKETING MIX PRODUK KERIPIK SINGKONG KELOMPOK PKBM SUARA HATI - Kaban, Reny Fitriana; Yuniarti, Rizki; Puji Erasashanti, Annathasia (Jurnal Pepadu, 2025)
Suara Hati PKBM, located in Nanggerang Village, Tajur Halang District, Bogor Regency, is a non-formal educational institution established in 2016 that has experienced an increase in the number of students every year. Most of the learners come from lower-middle-income families, street children, and underprivileged communities, yet they have high motivation to continue their education while gaining useful skills. One of the vocational training programs focuses on local potential entrepreneurship, namely cassava chips production. However, the lack of entrepreneurial skills and marketing strategies, including the use of digital marketing and business management, has hindered the development of this business. The aim of this community service activity is to enhance entrepreneurship capacity and marketing mix understanding among Suara Hati PKBM learners, particularly in developing cassava chip products. The program was carried out through stages of socialization, training (marketing mix, digital marketing, business management, and cassava chip production practice), technology implementation, mentoring, and evaluation. The results indicated a significant improvement in participants’ knowledge and skills, as shown by the average increase in pre-test to post-test scores of 38.69%. Participants were able to innovate products by adding flavor variants, improving packaging, setting competitive prices, expanding distribution through social media and e-commerce, and implementing simple financial records. The application of the marketing mix proved to enhance product competitiveness, while the strengthening of entrepreneurial skills boosted participants’ confidence in managing their businesses. This activity concludes that the combination of entrepreneurship skills and digital marketing strategies can serve as a replicable model for local skill-based MSME empowerment in various regions